HIV prone occupational exposures: epidemiology and factors associated with initiation of post-exposure prophylaxis. Issue 5 (2nd February 2009) - Zenner, D; Tomkins, S; Charlett, A; Wellings, K; Ncube, F
Abstract : Background: Occupational exposures to bloodborne viruses are very common. Whilst occupational HIV transmissions are rare, the serious physical, psychological and cost implications of potential transmission make this an important public health topic. European and UK guidelines recommend HIV post-exposure prophylaxis (PEP) as a valuable tool of preventing occupational HIV infection. Yet one in five UK healthcare workers did not initiate PEP despite having been exposed to an HIV-positive source patient. The aim of the study is to examine factors associated with PEP uptake behaviour. Methods: The study is based on an analysis of the UK Health Protection Agency surveillance database of 'Significant Occupational Exposures to Bloodborne Viruses in Healthcare Workers'. Associations between possible predicting factors and PEP-uptake have been examined with univariate analysis and logistic regression modelling. Results: Univariate analysis and logistic regression found significant associations between PEP-uptake and visible blood on the device (p<0.0001) and a linear relationship with increasing injury depth (p<0.0001). Doctors were significantly more likely to start PEP than nurses (OR 1.88, 1.16; 3.02). Multiple imputation of missing values did not significantly alter these results. Conclusions: PEP-uptake was associated with known transmission risk factors, suggesting awareness of current guidelines. The significant differences in PEP-uptake across occupation categories may be due to differential risk perceptions or other underlying factors. This is the first national study to examine PEP-uptake following occupational exposures to HIV. Further research and exploration of these findings are warranted, to understand the role of PEP-uptake behaviour in preventing occupational HIV transmission.